Bacteriochlorin‐bis(spermine) conjugate affords an effective photodynamic action to eradicate microorganisms. Issue 2 (10th November 2019) - Ballatore, María B.; Milanesio, María E.; Fujita, Hikaru; Lindsey, Jonathan S.; Durantini, Edgardo N.
Abstract: A novel bacteriochlorin bearing two spermine units (BCS ) was synthesized from 3, 13‐dibromo‐8, 8, 18, 18‐tetramethylbacteriochlorin (BC‐Br 3, 13 ). The synthesis involved the Suzuki coupling of BC‐Br 3, 13 to obtain a bacteriochlorin‐dibenzaldehyde (BCA ), which was subjected to reductive amination with spermine. The resulting bacteriochlorin BCS presents a strong near‐infrared absorption band at 747 nm, emits at 750 nm with fluorescence quantum yield of 0.14, and generates singlet molecular oxygen, O2 ( 1 Δg ), with a quantum yield of 0.27. Photokilling capacities mediated by BCS were evaluated in microbial cells. The viability of Staphylococcus aureus decreased 7 logs when cells were incubated with 1 μM BCS and irradiated for 15 minutes. Comparable photocytotoxic effect was obtained with Escherichia coli, when cells were treated for 30 minutes with visible light. BCS was also an effective photosensitizer to inactivate Candida albicans . In addition, this bacteriochlorin was able to eradicate bacteria at short incubation times. The structure of BCS contains eight basic amino groups that, when protonated in water, increase the binding to the cell envelope. In summary, the readily accessible bacteriochlorin BCS was highly effective at low concentrations as a broad‐spectrum antimicrobial photosensitizer. Abstract :